Influencia del control altitudinal en la distribución de unidades morfodinámicas degradativas y agradativas en áreas de montaña: el circo del Taillon (Valle de Gavarnie, Pirineo central francés) - Chueca Cia, Javier; Julián Andrés, Asunción (Geographicalia, 2017)
In this work the existente of an altitudinal control in the spatial distribution of morphodynamical areas in the Taillon glacial cirque is tested by quantitative method. The methodology adopted starts with the cartography and subsequent planimetry of the different agradative and degradative subunities defined, and allows us to stablish acurately the degree of maturity of the mountainous sector studied.